2010
DOI: 10.1016/j.jtcvs.2010.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid storm after coronary artery bypass grafting

Abstract: We describe a 45-year-old woman with thyroid storm developing after urgent coronary artery bypass grafting (CABG). The hallmark clinical features included fever, tachycardia, depressed mental status, and jaundice. Thyroid testing confirmed severe hyperthyroidism caused by Graves disease. The patient was rendered euthyroid after initiation of therapy with methimazole (INN, thiamazole), potassium iodide, and hydrocortisone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Onoe et al [13] reported that, in two patients with known thyrotoxicosis, open heart surgery was successfully performed by preoperative and early postoperative anti-thyroid agents. However, in a recent article, Bish et al [14] found thyroid storm developing in a patient after urgent CABG caused by Graves' disease which was unknown before surgery and controlled by immediate potassium iodide and thionamides through nasogastric tube, as well as high-dose intravenous hydrocortisone. In our study, we found no increase in the mortality rate in overt hyperthyroid patients, although we observed increased arrhythmia in this patient group after surgery, compared to the hypothyroid group, which was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Onoe et al [13] reported that, in two patients with known thyrotoxicosis, open heart surgery was successfully performed by preoperative and early postoperative anti-thyroid agents. However, in a recent article, Bish et al [14] found thyroid storm developing in a patient after urgent CABG caused by Graves' disease which was unknown before surgery and controlled by immediate potassium iodide and thionamides through nasogastric tube, as well as high-dose intravenous hydrocortisone. In our study, we found no increase in the mortality rate in overt hyperthyroid patients, although we observed increased arrhythmia in this patient group after surgery, compared to the hypothyroid group, which was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…There have only been a few case reports of thyrotoxicosis and thyroid storm in the perioperative period of open‐heart surgery, all of which occurred in coronary artery bypass grafting and were associated with coronary artery spasm and increased myocardial oxygen demand 4–8 . To the best of our knowledge, this is the first case report of thyroid storm occurring after cardiac valve surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Thyroid storm after nonthyroidal surgery, especially CABG, has been rarely reported. Successful treatment with intravenous beta-blocker and high-dose steroid was reported in a patient without preoperative history of hyperthyroidism [4]. According to the recent suggested guidelines, high-dose steroid treatment was recommended, if necessary, but caution is warranted because of a higher infection risk [9].…”
Section: Discussionmentioning
confidence: 99%
“…One of the cardiovascular events caused by thyroid storm following coronary artery bypass graft (CABG) is high output heart failure with extreme tachycardia, which can be fatal. Thyroid storm after nonthyroidal surgery, especially CABG, has been rarely reported, with only one reported case until now [4]. Herein, we present a case of thyroid storm onset in a patient who underwent CABG.…”
Section: Introductionmentioning
confidence: 88%